Advances in Neuroergonomics and Cognitive Engineering Proceedings of the AHFE 2018 International Conference on Neuroergonomics and Cognitive Engineering, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida USA - Ayaz, Hasan; Mazur, Lukasz (Advances in Intelligent Systems and Computing, 2019)
This book offers a broad perspective on the field of cognitive engineering and neuroergonomics, covering emerging practices and future trends toward the harmonious integration of human operators and computer systems. It presents novel theoretical findings on mental workload and stress, activity theory, human reliability, error and risk, and neuroergonomic measures alike, together with a wealth of cutting-edge applications. Further, the book describes key advances in our understanding of cognitive processes, including mechanisms of perception, memory, reasoning, and motor response, with a special emphasis on their role in interactions between humans and other elements of computer-based systems. Based on the AHFE 2018 affiliated conference on Neuroergonomics and Cognitive Engineering, held on July 21-25, 2018, in Orlando, Florida, USA, it provides readers with a comprehensive overview of the current challenges in cognitive computing and factors influencing human performance. .